Influence of the vinasse application in sugar cane fields in Patrocínio Paulista, São Paulo State, Brazil - Waal, A.; Jiménez-Rueda, J. R. [UNESP]; Bonotto, Daniel Marcos [UNESP]; Bertelli, C. [UNESP]; Hoffmann, H. M.; Foßhag, E.; Santilli, M. [UNESP] (WITPRESS LTD., 2009)
This investigation was carried out in Patrocínio Paulista municipality, located in the state of São Paulo, Brazil. Sugarcane has been extensively cultivated in the area in order to be utilized by the sugar and ethanol industries. The major effluent from the ethanol industry, vinasse, has been applied in the sugarcane fields as an alternative to supply several nutrients in crop production. Because it may represent a major environmental problem in that area, with implications to human health, soil samples from six points were collected and analyzed in order to evaluate the main factors related to the vinasse application in the ground. The importance of clays, iron oxides, organic matter and minor refractory minerals was also considered for explaining several relationships identified from the acquired data. © 2009 WIT Press.
Keywords: 40K radioactivity; São Paulo State; Soil contamination; Sugar and alcohol production; Sugar cane fields; Vinasse; Crop production; Environmental problems; Ethanol industry; Human health; Organic matter; Soil sample; Vinasses; Clay minerals; Cultivation; Effluents; Ethanol; Health; Health risks; Iron oxides; Organic minerals; Radiation; Radioactivity; Soil pollution; Soils; Sugar (sucrose); Sugar cane; Sugars